Using Text Messages for Critical Real-time Data Capture in the ANISA Study - Islam, Mohammad Shahidul; Rahman, Qazi Sadeq-ur; Hossain, Tanvir; Connor, Nicholas E; Hossain, Belal; Rahman, Md Mahmudur; Neogi, Ranjan; Saha, Samir K; El Arifeen, Shams (The Pediatric infectious disease journal, 2016)
The Aetiology of Neonatal Infection in South Asia (ANISA) study takes advantage of text messaging technology to record information required for randomizing the study population into a control subcohort. The text message system is also used for monitoring various study activities. When a child-health worker registers a newborn in the study, she sends a text message to a database server containing the study identification number and newborn's age at the time of registration. For each possible serious bacterial infection case, a study physician also sends a text message to the same server with the age of the young infant at the time of illness assessment. Using this information, a computer-based algorithm randomizes the newborn into a control subcohort. Text messages are also sent to alert the study physicians and study supervisors of a possible serious bacterial infection case being referred to health-care facilities. Phlebotomists working at remote specimen collection sites send text messages to the site laboratory personnel before sending the specimens through porters. Real-time data entry and monitoring are challenging for any population-based study conducted in remote areas. Our text messaging system provides an opportunity to overcome this barrier where availability of data entry facilities is limited.